2013
DOI: 10.1515/jib-2013-215
|View full text |Cite
|
Sign up to set email alerts
|

Can MiRBase Provide Positive Data for Machine Learning for the Detection of MiRNA Hairpins?

Abstract: SummaryExperimental detection and validation of miRNAs is a tedious, time-consuming, and expensive process. Computational methods for miRNA gene detection are being developed so that the number of candidates that need experimental validation can be reduced to a manageable amount. Computational methods involve homology-based and ab inito algorithms. Both approaches are dependent on positive and negative training examples. Positive examples are usually derived from miRBase, the main resource for experimentally v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

6
2

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Previously published algorithms, based on two-class classification, have been evaluated using sensitivity, specificity, and accuracy as measures for their predictive power. We have previously shown that positive data derived from miRBase contains contaminating non-miRNAs [27]. Additionally, it is clear that the negative class cannot be established experimentally and that the proposed negative datasets are likely to contain miRNAs.…”
Section: Evaluation Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previously published algorithms, based on two-class classification, have been evaluated using sensitivity, specificity, and accuracy as measures for their predictive power. We have previously shown that positive data derived from miRBase contains contaminating non-miRNAs [27]. Additionally, it is clear that the negative class cannot be established experimentally and that the proposed negative datasets are likely to contain miRNAs.…”
Section: Evaluation Methodsmentioning
confidence: 98%
“…Such approaches need positive (true miRNAs) and negative (non-miRNAs) data to become functional. Unfortunately, the positive data (usually derived from miRBase) may contain non-miRNAs [27]. Even worse, the negative class cannot be established experimentally and, therefore, most of these methods require the generation of an artificial negative class which may lead to problems [2].…”
Section: Computational Detection Of Pre-micrornasmentioning
confidence: 99%
“…At the end 7 different data sets with the most commonly used 10 [13] were produced for training. In the first dataset (1) 1600 positive and 800 negative examples were used.…”
Section: Data Miningmentioning
confidence: 99%
“…We recently showed that miRBase [11], the largest database for miRNAs, contains dubious examples for human and that, if all positive human miRNAs are used for classification, the accuracy is less than if the more stringently annotated examples from miRTarBase [12] are being used [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although other databases like miRTarBase [12], TarBase [13], and MirGeneDB [14] are available, positive data is generally derived from miRBase [15]. While negative data is of unknown quality, also positive data from miRBase contains questionable entries [14,16] and even MirGeneDB which filters miRBase entries is not free from questionable examples [17].…”
Section: Introductionmentioning
confidence: 99%